Impact of Money Supply and Inflation on Economic Growth - Asfaq Ahmad (Journal of Corporate Finance Management and Banking System, 2024)
Understanding the impact of money supply and inflation on Nepal's economic development is the main objective of the current study. This work aims to give empirical backing to the current debate over money supply, inflation, and the relationship between these factors and economic growth. More research has been done recently on the relationship between money supply and economic growth than on any other topic in the field of monetary economics. A price increase that, over time, results in a decline in buying power is known as inflation. This study looks at how inflation and the money supply affected economic development between 1974–1975 and 2022–2023. When establishing if there is long-term co-integration among variables when the bound test has been applied, the ARDL co-integration approach is employed in the study to ascertain the link between the variables. GDP is the dependent variable, and the independent variables are broad money (M2) and consumer price inflation (CPI), respectively. The notion that inflation is always a monetary event needs to be revisited and reevaluated, particularly in light of the distinct dynamics of inflation in developing economies. The research indicates a positive correlation between CPI and economic growth. The data indicates that CPI has a significant influence on economic growth in emerging nations like Nepal.